Analisis Tingkat Keramahan Lingkungan Alat Tangkap Bubu di Desa Gisik Cemandi Kecamatan Sedati Kabupaten Sidoarjo Jawa Timur - Guntur Priambodho; Tajuddin Noor; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
This study aims to analyze the level of environmental friendliness of the bubu fishing gear used by fishermen in Gisik Cemandi Village, Sedati District, Sidoarjo Regency, East Java. The evaluation was carried out using nine criteria for environmentally friendly fishing gear listed in the FAO 1995 Code of Conduct for Responsible Fisheries (CCRF), namely selectivity of fishing gear, impact on habitat, safety for fishermen, quality of catch, product safety for consumers, minimization of bycatch, impact on biodiversity, sustainability of protected species, and social acceptance in the community. This study used a survey method involving 30 fisher respondents selected using a purposive sampling technique. Data were collected through direct observation, structured interviews with questionnaires, and literature studies. Data analysis was carried out using a score weighting method based on the CCRF criteria. The results showed that the bubu fishing gear in Gisik Cemandi Village generally met the criteria as a very environmentally friendly fishing gear with a total score of 33.4 on a scale of 1–36.